Importance of Coding Education and Robotic Applications For Achieving 21st-Century Skills in North Cyprus - Kanbul, Sezer; Uzunboylu, Huseyin (International journal of emerging technologies in learning, 2017)
It is seen that coding education and robotic applications are integrated or being integrated into education system for students at early ages all around the world. Aim of this study is to reveal the importance of coding education and robotic applications for achieving 21st century skills in North Cyprus. This study is a descriptive study based on literature review. The obtained data were evaluated by the researcher to reveal the current case with a descriptive approach. It is really important for students to receive education on coding and robotics applications in order to be able to acquire 21st century skills, develop, produce and achieve “Informatics Island” vision of North Cyprus. In this research, it is seen that importance given to coding education and robotic applications in North Cyprus is insufficient. It is also revealed that there are effective robotic studies as a result of institutional efforts by universities. However, there is no attempt to integrate coding education into primary, secondary and university education programs and there is a little number of academic research related with coding education and robotic applications. It is expected that this study will be a guide for academicians who would like to conduct research in this field, provide information about the present condition and set an example.